A Tribo Bignonieae (Bignoniaceae) no Pico do Jabre: taxonomia e morfoanatomia foliar - Silva, Rafael Francisco Lopes (2019)
With about 393 species and 21 genera, Bignonieae Dumort. it is the largest tribe among the clades of Bignoniaceae, a family with many taxa of economic and ethnobotanical importance. Bignonieae is the group with the highest morphological diversity among Neotropical lianas and has a distribution that is limited between the southern United States and southern South America. The tribe concentrates its center of diversity in Brazil, with about 327 species occurring in wet and dry forests, including the most diverse associated ecosystems, such as altitude forests, in different phytogeographic domains. All Bignonieae species are woody, with opposite leaves, predominantly 2-3-leaflets, the terminal leaflet is modified in a single, trifid to multifid tendril, showy flowers, capsular fruits and anomalous stem anatomy, with four to 32 phloem bundles interrupting the xylem. This work was carried out with the objective of access the diversity of Bignonieae species in the Montane Semideciduous Seasonal Forest of Pico do Jabre, Northeast Brazil, and additionally to test the leaf anatomy of the tribe in support of its taxonomy. The results obtained are organized as three manuscripts to be submitted to publications in specialized journals. The first manuscript presents a taxonomic treatment for the 13 species of Bignonieae that occur in the studied area, which besides enriching the collections of the regional herbaria, also expanded the number of new records, including six new records for the Pico do Jabre, four for Paraíba State and one for Caatinga, The other two manuscripts present results of the anatomical studies performed for the 13 species of Bignonieae of the studied area. The second manuscript deals with the anatomy of the leaf epidermis and epidermal appendages, which provided qualitative and quantitative and distinctive characters to separate them at the generic and specific levels, such as the anatomy of stomatal complexes, idioblasts and trichomes. The third manuscript presents the pattern of the leaf anatomy of the Bignonieae of the Pico do Jabre, whose results showed the presence of relevant and diagnostic characters at the generic and specific levels, especially the anatomy of the petioles and petiolules, the main vein, vascular bundles, the qualitative and quantitative morphology of mesophyll, as well as the diversity and distribution of idioblasts, complemented by UPGMA analysis, which corroborated the effectiveness of leaf anatomical traits as an additional tool to the taxonomy of Bignonieae species.